Prevalensi Persistensi Gigi Sulung Pada Anak Usia 6-12 Tahun : Kajian pada Rekam Medik di RSGM FKG USAKTI (Penelitian) - Hamidah Oktafiani; Arianne Dwimega (Jurnal Kedokteran Gigi Terpadu, 2020)
Background: Tooth growth and development disturbances often occur in children. One such disorder is persistent primary teeth. This condition occurs in children aged 6 to 12 y.o, during mixed dentition stage. Persistent primary teeth is a condition when primary teeth is retained beyond the time of normal exfoliation, which can later induce teeth crowding. Objective: To determine the prevalence of persistent primary teeth in children aged 6 to 12 y.o at RSGM FKG Usakti. Method: This type of research is an observational descriptive study with a cross-sectional design. Sampels were obtained with consecutive sampling method. Sample used in this study was 215 medical records of patients aged 6 to 12 y.o at RSGM FKG Usakti during the period 1 May 2018 to 1 May 2019. Results: The results showed total of 215 samples consists of 50 (23.26%) with persistent primary teeth and 165 (76.74%) without persistent primary teeth. Persistent mostly occurs in girls aged 7 y.o (26%). Persistent primary teeth is most common in one tooth (52%) in the anterior region (57.4%) both in the maxilla (50%) and mandible (50%). Persistent primary teeth are most commonly found in maxillary central incisors (43.48%). Conclusion: The prevalence of persistent primary teeth in children aged 6 to 12 y.o at RSGM FKG Usakti was 23.26%.